Development of the "Mother Give Me Exclusive Breastfeeding" e-booklet based on Android as a nutrition educational media - Septa Katmawanti; Farah Paramita; Agung Kurniawan; Siti Khuzaimah A. Sharoni; Rosuzeita Fauzi; Dea Aflah Samah; Yassinda Thasia Audina; Muhammad Irfan Syahputra; Reza Pahlevi; Intan Gumilang Pratiwi (PAGEPress Publications, 2024)
Undernutrition is one of the most serious and least addressed challenges worldwide. The significant relationship between this condition and children's feeding practices makes exclusive breastfeeding an early and appropriate intervention. Therefore, this study aimed to develop health promotion media in the form of an Android-based booklet titled "Mother Give Me Exclusive Breastfeeding". The development method model adopted was ADDIE (Analysis, Design, Development, Implementation, Evaluation). A total of 20 mothers of toddlers participated in product feasibility testing. The results showed that the product had an average total percentage of 80%, signifying high suitability for usage. The study subjects rated the E-Booklet very positively, showing great enthusiasm for engaging with the content presented in the "Mother Give Me Exclusive Breastfeeding" E-Booklet. In conclusion, further study was needed to maximize the role of this product in enhancing mothers' understanding of exclusive breastfeeding and ensuring access to facilities such as gadgets, technology devices, and internet or wifi networks.